Keutamaan Salat Enam Rakaat Setelah Magrib: Studi ‘Ilal Hadis dan Implikasinya dalam Pembinaan Spiritual Muslim: The Virtue of Praying Six Rakaats After Maghrib: A Study of ‘Ilal Hadith and Its Implications in the Spiritual Development of Muslims - Rachmat Bin Badani Tempo (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2025)
The hadith that mentions the virtue of praying six rakaat after Maghrib, with the promise of a reward equivalent to twelve years of worship, is one of the hadiths that is often quoted in order to motivate Muslims to increase sunnah worship. Although this hadith is widely known, it is important to trace its validity based on scientific studies of the hadith, both in terms of sanad and matan. This study aims to examine the status of the hadith in depth using the ‘ilal al-hadith approach, and to link it to the relevance of Islamic teachings regarding sunnah deeds and spiritual development. This study uses a qualitative method through a literature study of classical and contemporary hadith literature. Based on the results of the study, this hadith is categorized as a weak hadith because in its sanad there are several narrators who are considered weak by hadith experts. However, some scholars allow the practice of weak hadith in the context of fadha'il al-a'mal (the virtue of deeds) with certain conditions. The content of this hadith has high motivational value within the framework of tazkiyah an-nafs, namely the purification of the soul, and can be part of an Islamic development strategy in everyday life. Thus, this hadith can still play a role in forming a strong culture of worship among Muslims.